Pelatihan Digital Marketing Bagi Pelaku UMKM Desa Ciseeng Kabupaten Bogor - Muslikh Muslikh; Intan Annisa; Ariel Nian Gani (Lembaga Penelitian Universitas YARSI, 2020)
The aim of this program is to improve digital marketing capabilities for micro-entrepreneurs (MSMEs) in Ciseeng Village, Bogor Regency. This program is based on the problems faced by partners which are reflected in the situation map and the solutions offered to overcome the problems faced by partners. The solution offered is training and digital marketing assistance with materials: creating a website portal, creating a digital marketing community, creating online promotion methods, designing strong branding, making attractive packaging or packaging for MSMEs in Ciseeng Village, Bogor Regency. The approach used is: learning, implementation and mentoring or evaluation. The results of the training indicate a significant increase in digital marketing capabilities.